Recurrent carotid artery stenosis successfully and safely treated with drug-coated balloon angioplasty under flow reversal - Marianna Pavlyha, MD; Steven Farley, MD; Wesley S. Moore, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Carotid artery restenosis after index carotid artery revascularization reduces its stroke prevention benefit. A 73-year-old woman presented with recurrent right carotid artery restenosis following two carotid endarterectomies with patch angioplasty and in-sent restenosis after subsequent transcarotid artery revascularization. We performed in-stent paclitaxel-coated balloon angioplasty under flow reversal with resolution of the lesion on imaging and improvement in symptoms. Patient remains asymptomatic with no evidence of restenosis 16 months after treatment.